2018
DOI: 10.1093/intqhc/mzy138
|View full text |Cite
|
Sign up to set email alerts
|

The quality and safety culture in general hospitals: patients', physicians' and nurses' evaluation of its effect on patient satisfaction

Abstract: Patients have sufficient experience and understanding to form an opinion of the quality and safety of their care. The lower evaluation of the quality and safety culture expressed by health care workers might stem from their more realistic expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
3
13
0
2
Order By: Relevance
“…The safety and quality climate of the ward was evaluated by a previously validated tool in Hebrew (Kagan et al, 2019) that was based on sections from well-known and validated surveys measuring quality and patient safety climate: the Stanford/Patient Safety Center of Inquiry Culture Survey (Singer et al, 2003) and the Agency for Healthcare Research and Quality quality and safety climate tool (Sorra & Nieva, 2004). The tool in this study comprised 44 items examining six domains:…”
Section: Part II Safety and Quality Climate Of The Wardmentioning
confidence: 99%
“…The safety and quality climate of the ward was evaluated by a previously validated tool in Hebrew (Kagan et al, 2019) that was based on sections from well-known and validated surveys measuring quality and patient safety climate: the Stanford/Patient Safety Center of Inquiry Culture Survey (Singer et al, 2003) and the Agency for Healthcare Research and Quality quality and safety climate tool (Sorra & Nieva, 2004). The tool in this study comprised 44 items examining six domains:…”
Section: Part II Safety and Quality Climate Of The Wardmentioning
confidence: 99%
“…However, empirical research on patient safety and patient safety climate in medical settings still lags far behind the theoretical literature on these topics (Zaheer et al., 2015). A previous study explored the disparities between the perceptions of patients and health care workers on the quality and safety culture, and the relationship between patient perceptions and engagement in, and satisfaction with their care and treatments (Kagan et al., 2019). It is essential to continuously improve health care quality through the implementation of patient safety culture.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, it was expected that the evaluations of the professionals of the smaller centers would have the lowest evaluation for two reasons: (1) the information was not disseminated with the same intensity; and (2) the actions started at the larger centers, which resulted in a greater volume of activities. In several studies conducted in a different setting, front-line professionals were found to usually complain more about actions proposed by the directive staff [6]. Also, some studies have shown the sensibility of the safety culture measures to discriminate against the impact of positive actions to improve safety [19] In this case, we observe a similar pattern, although, curiously, there were not greater differences when comparing safety culture measures between quality coordinators and professionals working in smaller centers.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of front-line professionals in safety is a prerequisite for the achievement of an increased quality environment for patients [3]. Healthcare providers’ attitudes, viewpoints, and behaviors in quality, and particularly their safety culture, are crucial for the transformation of healthcare organizations in order to achieve their quality targets, including patients’ satisfaction [4,5,6]. …”
Section: Introductionmentioning
confidence: 99%